DEFINITION OF THE CRITERIA FOR DEVELOPMENT EFFECTIVENESS OF PROFESSIONAL COMPETENCE OF TEACHER IN THE CONTEXT OF HEALTH CREATING APPROACH TO EDUCATION - Ol’ga V. Vashechkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the article clarifies the concept of "professional competence of teachers" in the context of health creating approach to education, describes performance criteria of its development; demonstrates a model of a comprehensive assessment of the impact of development of professional competence of the teacher in the context of health creating approach to education.